ANALISIS IMPOR BERAS DAN KESEIMBANGAN PASAR BERAS INDONESIA - Helmi Noviar; Affandi Affandi (JURNAL EKOMBIS, 2019)
The study aims to find and test simultaneous equation models in an effort to obtain the right model to estimate fit in the analysis of the needs of a national rice reserve. By using the data of the Central Board of Statistics of various editions and data of the Food Agricultural Organization all data needs of variables can be fulfilled.The method of estimation is using Two stage Ordinary Least Square (TSLS). Taking into consideration the condition of the variables, this model is identified overidentified, using some variable lag. The estimated results show some parameters quite significant, there are still some variables that are not statistically significant. Therefore, it is necessary pedekatan more precise model specifications, and other estimation methods, such as the Seemingly Unrelated Regression (SUR) technique. Keywords: Simultaneous Model, partial adjusment, TSLS